Rancang Bangun Sistem Informasi Penjualan Obat di Apotek Era Medika Berbasis Website - Putra, I Gede Feby Dian Pramana (Prodi Sistem Informasi FST Universitas Jambi, 2024)
Handling data by doing this manually has a number of obstacles at the Era Medika Pharmacy, including causing errors in checking drug stock once a week, inaccurate recording of incoming or outgoing drug stocks so that there is a mistake in recording the final stock, as well as the results of sales reports use paper. To overcome this problem the drug sales information system is a solution to the drug sales process, and uses the Click to Chat API Whatsapp to facilitate sending messages to drug suppliers. To obtain the data needed during the study, the author uses several method including: interviews, observation, and literature studies. The data obtained then analyzes using the Waterfall method. The results of this study conducted on testing sales applications that have been designed can help to facilitate managers in the sales process that can be accessed online so that it can work effectively and efficiently. With the Click to Chat feature Whatsapp can facilitate messages to drug suppliers according to the contact you want to reach. The results of this study are expected to be useful in the future.